An online guided ACT intervention for students : what are the student experiences, and do they differ depending on anxiety level? - Lantto, Kersti (2021)
Psychological problems are a serious and increasing health threat to university students. Online interventions present a promising low-cost, easy-access support option. This study explored the student experiences of Student Compass, an online guided ACT intervention developed in the University of Jyväskylä. The study also investigated whether the experiences differ depending on pre-intervention anxiety levels. The intervention was 7 weeks long and included online material and support from student coaches in the form of three meetings and online feedback. The participants (n = 148) filled in GAD-7 before the intervention and a questionnaire about their experiences after the intervention. The student experiences of the Student Compass were highly encouraging; almost all the students were satisfied with the intervention and would recommend it to their friends. Most students thought they had gained significant benefits from the program, such as learning new skills, gaining insight, and noticing improvements in their mental well-being. The most useful aspect of the intervention was thought to be the coach support, and most students felt the amount of support was sufficient. The experiences did not differ depending on anxiety level, indicating that high anxiety is not a barrier for online interventions, at least when the amount of support is moderate. While more research is warranted, the mandate from students for making supported online interventions more widely available is strong.